2021
DOI: 10.1186/s12903-021-01810-x
|View full text |Cite
|
Sign up to set email alerts
|

Associations of early childhood caries with salivary beta defensin-3 and childhood anemia: a case–control study

Abstract: Background Human beta defensin-3 (HβD-3) is an antimicrobial peptide present in saliva that protects tooth surfaces from microbial attack. These peptides are part of innate immunity so levels may be affected by different systemic diseases like anemia. Therefore, anemia may predispose an affected child to an increased risk of dental caries. The objectives of this study were to determine the association of early childhood caries (ECC) with HβD-3 levels and observe the association of HβD-3 levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Children with iron-deficiency anemia have a higher prevalence of episodes of acute otitis media compared to healthy, non-anemic children, and there is a direct relationship between the degree of anemia and the number of episodes [16]. A further study shows that anemia may affect the innate immunity of children and may result in a decreased level of salivary human beta defensin-3 (HβD3), thus increasing vulnerability to decay [17]. In our study, the average number of viral diarrheas decreased significantly after the diagnosis of IDA compared to before the diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Children with iron-deficiency anemia have a higher prevalence of episodes of acute otitis media compared to healthy, non-anemic children, and there is a direct relationship between the degree of anemia and the number of episodes [16]. A further study shows that anemia may affect the innate immunity of children and may result in a decreased level of salivary human beta defensin-3 (HβD3), thus increasing vulnerability to decay [17]. In our study, the average number of viral diarrheas decreased significantly after the diagnosis of IDA compared to before the diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…A Saudi Arabian crosssectional study showed that the anemic children had significantly higher mean dmft indices (11.20±2.6) than non-anemic children (9.66±1.2%, p=0.05). 10 Another Pakistani study found that anemia may alter children's innate immunity, resulting in a lower amount of human beta defensin-3 (HD-3), an antimicrobial peptide presents in saliva that protects tooth surfaces from microbial attack. Salivary HD3 shortage, hence increasing degradation risk.…”
Section: Introductionmentioning
confidence: 99%
“…Salivary HD3 shortage, hence increasing degradation risk. 10 Moreover, another systematic review concluded that children with dental caries had a 4.5-fold higher prevalence of anemia diagnosis than children without. 11 The association between anemia and dental caries incidence has been explained by different ways.…”
Section: Introductionmentioning
confidence: 99%